Bhutan : Technical Assistance Report-Royal Monetary Authority-Steps Towards a Liquidity Forecasting and Management Framework. (IMF Staff Country Reports; Country Report, 2019)
This Technical Assistance report highlights that setting up a liquidity forecasting framework would go a long way in establishing a key building block allowing the Royal Monetary Authority of Bhutan (RMA) to fulfil its legal mandate to formulate and implement monetary policy in ways better aligned with current central bank practices. The structural liquidity surplus, mainly due to foreign reserves accumulation, has been broadly stable in the absence of RMA intervention. The paper discusses that the volatility of autonomous factors and the fragmentation of the money market justify ambitious steps by the RMA towards setting up a liquidity management framework. The mission identified several constraints and gaps that need to be addressed to support the effectiveness of a liquidity forecasting framework. The mission's recommendations presented in the report aim at streamlining the processing of the Government's financial transactions and cash balances. Looking ahead, monetary policy transmission would benefit from developing RMA's liquidity forecasting and management capacity.